Perancangan Perangkat Lunak Kelayakan Pemberian Kredit Mobil dengan Menggunakan Metode Analytic Hierarcy Process (AHP) - Sitanggang, Lestari Pratiwi (MEANS (Media Informasi Analisa dan Sistem), 2019)
Research with the title "Designing software for providing car credit worthiness using the Analytic Hiercy Process (AHP) method" was made with the main goal of building a software that is expected to help determine whether a person is worthy of credit, where this software is formed from a system decision support and to evaluate the feasibility of someone in receiving credit that will help decision makers in determining credit lending decisions by analyzing credit terms that have met the Five C requirements, namely customer character (Character), capacity to pay off credit (Capacity), the ability of capital to be customer owned (Capital), collateral owned by the customer to bear credit risk (Collateral), and the customer's financial condition (Condition).